Approach considerations for the management of strangulation in the emergency department. Issue 2 (16th April 2022) - Stellpflug, Samuel J.; Weber, William; Dietrich, Ann; Springer, Brian; Polansky, Robin; Sachs, Carolyn; Hsu, Antony; McGuire, Sarayna; Gwinn, Casey; Strack, Gael; Riviello, Ralph
Abstract: Patients with a history of strangulation present to the emergency department with a variety of different circumstances and injury patterns. We review the terminology, pathophysiology, evaluation, management, and special considerations for strangulation injuries, including an overview of forensic considerations and legal framework for strangulation events.